ANALISIS PENINGKATAN KUANTITAS PENJUALAN HANDPHONE PADA ELDORA CELL DI MASA PANDEMI COVID-19 - Erika Septi Triviana; Indah Permata Sari; Novita Putri Wulandari; Reta Karunia Astuti; Yeyen Karisa Putri; Carmidah, Carmidah (Pusat Riset dan Inovasi Nasional, 2022)
In 2020, a new type of pneumonia was found in Wuhan, Hubei Province which then spread to more than 190 countries and regions which had an impact on the economic sector, especially the trade sector, both due to decreased and increased sales. One of the businesses that has experienced the impact of a significant increase in sales during the pandemic is Counter Eldora Cell. This study aims to determine Eldora Cell counter sales in 2020 from January to December. The data collection method in this study is an interview. The type of data in this study is qualitative data. The data sources used in this study are primary data and secondary data. The results of the study show that sales at the Eldora Cell Counter have increased in the sales period from January to December 2020